2007
DOI: 10.1097/mbc.0b013e328010bd16
|View full text |Cite
|
Sign up to set email alerts
|

A case of afibrinogenemia associated with A-alpha chain gene compound heterozygosity (HUMFIBRA c.[4110delA]+[3200+1G>T])

Abstract: The clinical features and molecular biology data of a case of afibrinogenemia are reported. The propositus is a 14-year-old girl who suffered several bleeding manifestations that were successfully treated with fibrinogen infusion. The afibrinogenemia results from compound heterozygosity for two mutations on the Aalpha chain gene (c.[4110delA]+[3200+1G>T]). The first mutation is a novel frameshift mutation inherited from her father. The second is a previously described Aalpha chain gene splice junction mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Since it was identified as first genetic cause of the afibrinogenemia, the 11-kb FGA deletion was confirmed as a recurrent genetic variant in afibrinogenemic patients [ 25 , 26 , 27 ]. However, the IVS4 + 1G > T (c.510 + 1G > T, numbered according to the Human Genome Variation Society, HGVS, recommendations) splicing site variant is more common than the 11-kb deletion, especially in individuals of Caucasian ancestry [ 26 , 27 , 28 , 29 , 30 , 31 ]. In the FGA intron 4, a bioinformatics-based study showed that the IVS4 + 1G > T may affect the functionality of the splicing donor site and lead transcriptional machinery to use multiple cryptic splicing sites [ 32 ].…”
Section: Afibrinogenemiamentioning
confidence: 99%
“…Since it was identified as first genetic cause of the afibrinogenemia, the 11-kb FGA deletion was confirmed as a recurrent genetic variant in afibrinogenemic patients [ 25 , 26 , 27 ]. However, the IVS4 + 1G > T (c.510 + 1G > T, numbered according to the Human Genome Variation Society, HGVS, recommendations) splicing site variant is more common than the 11-kb deletion, especially in individuals of Caucasian ancestry [ 26 , 27 , 28 , 29 , 30 , 31 ]. In the FGA intron 4, a bioinformatics-based study showed that the IVS4 + 1G > T may affect the functionality of the splicing donor site and lead transcriptional machinery to use multiple cryptic splicing sites [ 32 ].…”
Section: Afibrinogenemiamentioning
confidence: 99%
“…Plasma fibrinogen levels of all heterozygous individuals were almost normal, and 1 of 16 people had <1.5 g/l by either the functional method or immunological determination method. Further, we showed plasma fibrinogen concentrations of probands with afibrinogenemia and their heterozygous family members in Table 2 [11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Genetic mutations in Table 2 included nonsense, frameshift, and splicing abnormality in FGA, FGB, or FGG, all of which lead to premature termination and NMD [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Although many clinical cases have been described and the spectrum of bleeding symptoms is well known, the underlying genetic basis has been identified only in a minority of cases. To date most of the 58 mutations reported were family‐specific and were widespread throughout the fibrinogen cluster (Asselta et al , 2006; Fang et al , 2006; Angles‐Cano et al , 2007; Monaldini et al , 2007; Neerman‐Arbez & de Moerloose, 2007). In contrast to large deletions (representing 6·9% of total mutations and involving only FGA ), point mutations are frequent (93·1%) and, with the exception of missense mutations that are confined to FGB , are spread throughout the fibrinogen genes (31 point alterations in FGA , 15 in FGB , and only eight in FGG ).…”
mentioning
confidence: 99%